Pencarian Rute Terpendek pada Citra Labirin Menggunakan Algoritma Dijkstra sebagai Pemandu Gerak Micromouse Robot - Santoso, Dwijaya; Harianto, Harianto; Ihyaudin, Ihyaudin (Journal JCONES, 2012)
Micromouse Robot has a goal to complete the maze that is the path to find a route from start point to finish with the shortest route. In search of the shortest route, Micromouse robot must perform scanning area of the maze path directly to determine the weights as input a shortest route algorithm. Processing on the image of the labyrinth and the Dijkstra algorithm to be the main discussion in this study. In practice, create an image processing algorithm to detect the nodes on the image of the labyrinth that the result becomes the input to the Dijkstra algorithm in order to get Micromouse Robot motion directions. These Applications on computers have been able to detect the nodes on the image of the labyrinth if the track width of a cell evenly, and experienced an error if there is a point that the width of the tracks is uneven in the amount of two cells. The shortest route formed by the application of the computer is in accordance with the route established by the program on Micromouse Robot. Keyword: Dijkstra Algorithm, Image Processing, Microcontroller.